2017
DOI: 10.1038/s41467-017-01749-0
|View full text |Cite
|
Sign up to set email alerts
|

GABAA receptor dependent synaptic inhibition rapidly tunes KCC2 activity via the Cl−-sensitive WNK1 kinase

Abstract: The K+–Cl− co-transporter KCC2 (SLC12A5) tunes the efficacy of GABAA receptor-mediated transmission by regulating the intraneuronal chloride concentration [Cl−]i. KCC2 undergoes activity-dependent regulation in both physiological and pathological conditions. The regulation of KCC2 by synaptic excitation is well documented; however, whether the transporter is regulated by synaptic inhibition is unknown. Here we report a mechanism of KCC2 regulation by GABAA receptor (GABAAR)-mediated transmission in mature hipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
179
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(190 citation statements)
references
References 61 publications
9
179
2
Order By: Relevance
“…Thus, Ca 2+ influx through postsynaptic NMDA receptors or during prolonged postsynaptic firing (Fiumelli et al, 2005) rapidly reduces KCC2 membrane expression and function through proteinphosphatase-1-dependent dephosphorylation of its Ser940 residue and protein cleavage by the calcium-activated protease calpain Lee et al, 2011;Puskarjov et al, 2012). Conversely, Cl À influx through GABAA receptors stabilizes KCC2 at the plasma membrane via chloride-mediated inhibition of the serine-threonine WNK1 kinase and its downstream effectors SPAK-OSR1, which phosphorylate KCC2 on Thr906 and Thr1007 residues (Caraiscos et al, 2004;Heubl et al, 2017;Kahle et al, 2016). Finally, KCC2 expression is also regulated by several neuromodulators acting on G-protein-coupled receptors (Mahadevan and Woodin, 2016) as well as neurotrophins, such as brain-derived neurotrophic factor (BDNF), acting via TrkB signaling (Rivera et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Ca 2+ influx through postsynaptic NMDA receptors or during prolonged postsynaptic firing (Fiumelli et al, 2005) rapidly reduces KCC2 membrane expression and function through proteinphosphatase-1-dependent dephosphorylation of its Ser940 residue and protein cleavage by the calcium-activated protease calpain Lee et al, 2011;Puskarjov et al, 2012). Conversely, Cl À influx through GABAA receptors stabilizes KCC2 at the plasma membrane via chloride-mediated inhibition of the serine-threonine WNK1 kinase and its downstream effectors SPAK-OSR1, which phosphorylate KCC2 on Thr906 and Thr1007 residues (Caraiscos et al, 2004;Heubl et al, 2017;Kahle et al, 2016). Finally, KCC2 expression is also regulated by several neuromodulators acting on G-protein-coupled receptors (Mahadevan and Woodin, 2016) as well as neurotrophins, such as brain-derived neurotrophic factor (BDNF), acting via TrkB signaling (Rivera et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In mature neurons, KCC2 plays a prominent role in maintaining transmembrane chloride gradients, thereby influencing ion flux through the chloride-permeable GABAA receptor channels. Thus, KCC2 pharmacological blockade 45,46 , genetic ablation 61,62 or suppression 63 , or activity-dependent modulation 6,11,46,64 all result in a depolarization of the reversal potential of GABAAR-mediated currents (E GABA ). Consistent with these observations, we found that chronic KCC2 knockdown in dentate granule cells resulted in a depolarizing shift of E GABA by about 9 mV.…”
Section: Discussionmentioning
confidence: 99%
“…In mature neurons, KCC2 expression and function is rapidly regulated by neuronal activity via multiple posttranslational mechanisms 4,5 . Thus, Ca 2+ influx through postsynaptic NMDA receptors or during prolonged postsynaptic firing 6 rapidly reduces KCC2 membrane expression and function through protein phosphatase 1-dependent dephosphorylation of its Ser940 residue and protein cleavage by the calcium-activated protease calpain 7,8,9 . Conversely, chloride influx through GABAA receptors stabilizes KCC2 at the plasma membrane via chloride-mediated inhibition of the serine/threonine WNK1 kinase and its downstream effectors SPAK/OSR1, which phosphorylate KCC2 on Thr906 and Thr1007 residues 10,11,12 . Finally, KCC2 expression is also regulated by several neuromodulators acting on G-protein couples receptors 13 as well as neurotrophins such as BDNF acting via TrkB signaling 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibitory neural transmission in the adult nervous system is mediated by γ-aminobutyric acid (GABA) [1] and glycine, with fast synaptic inhibition occurring largely through the ionotropic GABA A receptor (GABA A R) [2,3]. As a GABA-gated chloride (Cl − ) channel, the consequence of GABA A R signaling is dependent on intracellular Cl − concentration, which determines the reversal potential for GABA A R currents (E GABA ).…”
Section: Introductionmentioning
confidence: 99%